Teaching Multiculturalism To Fight Against Racism In The Freedom Writer By Richard Lagravenese - Ratu Vanessa, Al Devia; Candraningrum, Dewi (Jurnal Ilmiah Mandala Education (JIME), 2023)
Multiculturalism is refers to cultural differences caused by the existence of different groups in society, where people's attitudes and practices create a distinctive group identity. While, Fredom Writers movie which was released on 2007 portrayed the multiculturalism in a school taught by Erin Gruwell. This movie directed by Richard LaGravenes. This study examined the teaching multiculturalism in the movie to fight racism in the school. This research belongs to qualitative research and the result og this research are: first, the multiculturalism approach applied so well in the movie by Erin Gruwell. Second, the multiculturalism can change the attitude and behavior of the students in the movie. Third, Freedom Writers movie provide great example of the effectiveness of multiculturalism approach in education.